Implicações éticas da filosofia de liberdade em O conceito de angústia de Sören Kierkegaard - Rocha, Juvenal Dias da (2013)
This is an investigation, in which is described the ethical implications of the Kierkegaard\'s philosophy of freedom, as freedom of to believe, to think, to act, and to express freely an idea according to the conscience, in his philosophical-ethical view. Reflects on the human condition and how the anguish of existence affects or explains the be free, Even though he lives in the same community, sharing common spaces, but having that differ in beliefs, principles, interests, politics, philosophy, and life goals. The purpose of this concern (τελοs) is to avoid radicalism expressed mainly in the misuse of the term \"discrimination\" (δοκικαζω) and contribute to the establishment of a full freedom of expression. Kierkegaard is considered the father of Existentialism, and in all his works he speaks about the anguish of the human being in view of the conquest of freedom. The work has as its starting point the work The Concept of anguish and as philosophical basis, the Christian Existentialism, which to deal about the fall of man and the anguish produced by the constant pursuit of reconciliation, which Kierkegaard calls \"leap of faith\". His philosophy of freedom results from idea that the existence of a man develops throughout his life and is based on the concept of desperation implied by mortal sin, implicit in the Scripture; since to falter in the spirit means to abandon the faith in God, albeit briefly. The investigation contemplated in the first instance, the philosophy of freedom in The Concept of Anguish theoretical basis of philosophy of freedom developed by the author. In a second moment, is established the definition of the concept of Freedom of Conscience, as unfolding of the philosophy of freedom up to ethical implications. And finally, was drafted a proposal for the consideration of freedom of conscience, including clarification of the definition and description of the concept of freedom of conscience, anchored in theoretical basis used, thus arriving at the conclusion that, indeed, there are ethical implications in the Kierkegaard\'s philosophy of freedom.